2011
DOI: 10.1016/j.jom.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ orders––If they’re electronic, do they improve patient satisfaction? A complements/substitutes perspective

Abstract: Doctors’ orders entered with Computerized Physician Order Entry (CPOE) systems are designed to enhance patient care by standardizing routines that are intended to improve quality of healthcare. As with other health information technology (IT) performance studies, literature shows conflicting results regarding the CPOE–performance relationship. By adopting a more nuanced perspective and employing not just adoption but extent of use of CPOE, we first examine whether or not CPOE use improves patient satisfaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 89 publications
2
77
0
Order By: Relevance
“…HIT tools such as computerized decision support systems (CDSS) can reduce uncertainty and ambiguity in treatments by providing supportive information for specific patient conditions. Queenan et al (2011) found that both CPOE and aggregate HIT infrastructure are associated with higher overall Patient Satisfaction .…”
Section: Hypothesis Development Via Information Processing Theorymentioning
confidence: 95%
“…HIT tools such as computerized decision support systems (CDSS) can reduce uncertainty and ambiguity in treatments by providing supportive information for specific patient conditions. Queenan et al (2011) found that both CPOE and aggregate HIT infrastructure are associated with higher overall Patient Satisfaction .…”
Section: Hypothesis Development Via Information Processing Theorymentioning
confidence: 95%
“…Aggressiveness, or the willingness to perform more procedures (Currie et al, 2016), in choosing a treatment is more of a physician-specific preference (Currie et al, 2016), and there is no reason to believe that justification would change an individual physician's preference for a test. The collaborative nature of justification may also improve physicians' judgment about whether a patient is high probability or not, since greater collaboration among clinicians leads to improved outcomes (Dobrzykowski, McFadden, & Vonderembse, 2016;Queenan, Angst, & Devaraj, 2011;Senot, Chandrasekaran, & Ward, 2016). Research has shown that nurses consider the personal cost to themselves when deciding to contribute improvement ideas regarding operational failures (Tucker, 2016).…”
Section: Mechanisms: the Moderating Effect Of Patient Conditionmentioning
confidence: 99%
“…The size of improvements in performance varied considerably due to implementation of clinical guidelines (Grimshaw and Russell, 1993). In addition to supporting the clinicians, it can be also be used as a tool of verification by administrators, who can study the computerized physician order entry (CPOE) reports and ascertain if the patient was informed by the clinician that s/he was eligible to receive the selected preventable care, thus appraising how well clinicians follow hospital guidelines (Dexter et al, 2001;Overhage et al, 1997Overhage et al, , 1996Queenan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research and Education, 2011). Therefore, the CPOEs recommend suitable drug formulation and ensure administration of appropriate drug dose (Teich et al, 2000;Chertow et al, 2001;Queenan et al, 2011). Content process is defined as the process that "nurses use to gather information based on the patient case history, evaluate the information, and make a judgment that results in patient care" (White et al, 1992).…”
Section: Introductionmentioning
confidence: 99%